Plutarch’s Epicurean justification of religious belief - Carter, J (Johns Hopkins University Press, 2018)
In his dialogue, Non posse suaviter vivi secundum Epicurum, Plutarch of Chaeronea criticizes Epicurus for not believing that the gods are provident over human affairs and for not believing that our souls survive death. However, Plutarch’s arguments are striking in that they do not offer any theoretical justification for believing either of these religious claims to be true; rather, they aim to establish that we are practically justified in adopting them if we follow Epicurus’s rule that the goal of belief is not truth in its own right, but mental tranquility. I argue that this form of argument assumes a novel justificatory theory of religious belief, based in Epicurean thought, that I call ‘strong doxastic hedonism.’